Applicability of bovine microsatellite markers for population genetic studies on African buffalo (Syncerus caffer) - Hooft, W.F. van; Hanotte, Olivier H.; Wenink, P.W.; Groen, A.F.; Sugimoto, Y.; Prins, H.H.T.; Teale, A.J. (Wiley, 1999)
The applicability of bovine autosomal micro-satellite markers for population genetic studies on African buffalo was investigated. A total of 168 microsatellite markers were tested for PCR amplification on a test panel of seven African buffalo. Amplification was observed for 139 markers (83 percent), and 101 markers were studies further with 91 (90 percent) being polymorphic. The mean number of alleles per marker was 5.0 (SE=0.2) and the mean heterozygosity per marker was 0.61 (SE=0.03). Considering the overall high level of polymorphism, it was concluded that most bovine microsatellite markers are applicable in African buffalo.